Peran Dhuafa Mart Dalam Memasyarakatkan Sistem Ekonomi Syariah - Khairi, Rifqil; Zakir, Muhammad; Syaipudin, Muhammad; Amelia, Nur (Journal of Community Sustainability, 2024)
This service was carried out for Dhu'afa Mart Air Tiris Kampar, the aim of this community service was to find out the extent of the role of Dhu'afa Mart Air Tiris Kampa in promoting the Sharia Economic System. The methods used in this community service activity are observation, presentation and discussion. The results of the service show that: The service program for Dhu'afa Mart Air Tiris Kampar can be carried out well and runs smoothly in accordance with the activity plan that has been prepared. The results of this service conclude that: First, Dhu'afa Mart Air Tiris really contributes to Introducing Sharia Economics among various Local Communities. Second, the achievement of the objectives of the service activity program for Dhu'afa Mart Air Tiris Kampar, all programs that have been carried out in collaboration between business owners and servants have been carried out and in accordance with the event rounddown and predetermined time .